2019
DOI: 10.7309/jmtm.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Teleophthalmology Through Handheld Mobile Devices: A Pilot Study in Rural Nepal

Abstract: Background: To compare screening referral recommendations made by remotely located ophthalmic technicians with those of an ophthalmologist examining digital photos obtained by a portable ophthalmic camera system powered by an iOS handheld mobile device (iPod Touch). Methods: Dilated screening eye exams were performed by ophthalmic technicians in four remote districts of Nepal. Anterior and posterior segment photographs captured with a Paxos Scope ophthalmic camera system attached to an iPod Touch 6 th generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…[6][7][8] A retinal screening study from Nepal using a Paxos Scope ophthalmic camera system (DigiSight Technologies, San Francisco, CA, USA) attached to a 6th generation iPod Touch showed that of 101 patients referred to an ophthalmologist based on screening results, the ophthalmologist concurred with the appropriateness of the referral in 97% of cases. 9 A 2019 study in JAMA Ophthalmology found that remote diagnostic imaging (fundus photography and OCT) using an FDA approved non-contact retinal imaging device (iFusion; Optovue) versus standard examination by a retinal specialist were equivalent in detecting referable macular degeneration. 8…”
Section: Efficacy and Reliabilitymentioning
confidence: 99%
“…[6][7][8] A retinal screening study from Nepal using a Paxos Scope ophthalmic camera system (DigiSight Technologies, San Francisco, CA, USA) attached to a 6th generation iPod Touch showed that of 101 patients referred to an ophthalmologist based on screening results, the ophthalmologist concurred with the appropriateness of the referral in 97% of cases. 9 A 2019 study in JAMA Ophthalmology found that remote diagnostic imaging (fundus photography and OCT) using an FDA approved non-contact retinal imaging device (iFusion; Optovue) versus standard examination by a retinal specialist were equivalent in detecting referable macular degeneration. 8…”
Section: Efficacy and Reliabilitymentioning
confidence: 99%
“…3,4,7 Easily accessible fundus imaging would provide enhanced documentation by saving time and by increasing accuracy through the minimisation of interpretation or communication errors. 3,4,14 The confidence of interpretation currently is dependent on the degree of training received, and subsequent frequency and self-rated competence of individual physicians. 3…”
Section: The Digital Spectrum Of Ophthalmoscopesmentioning
confidence: 99%
“…3,7 Digital ophthalmoscopy, however, has been proven to build greater competence and confidence in students, optimising their learning within a smaller time-period. 3,4,14 Independence is essential for a lifelong career in healthcare and the current shortfall in training recruitment will likely continue to contribute to inefficiencies in service provision and patient care. 1,3,4,7 Given the risks associated with failing to visualise the fundus appropriately, training to promote competence and independence is essential to ensure high-quality patient care.…”
Section: Training and Competencementioning
confidence: 99%
See 2 more Smart Citations